Pengaruh Implementasi Reward dan Punishment PT. XYZ Atas Kinerja Karyawan - Ilyas Habibi; Risma Fitriani (Universitas Negeri Gorontalo, 2023)
In competing with competitors, each company will certainly do various ways so that the performance of its employees can be maintained properly, one of which is to provide rewards and punishments. This research was conducted by the authors to be able to show the effect of reward and punishment on employee performance at PT. XYZ in Karawang because at the time the research was carried out the reward and punishment system that was currently implemented by PT. XYZ was still not optimal. Because all members of the population consisting of 16 people were sampled in the study, the sample for this study was a saturated sample. Multiple linear regression is the method used for problem solving in this study. The results showed that after testing with multiple linear regression methods each (partial) there was no effect on each independent variable, be it reward or punishment on the dependent variable on employee performance at PT. XYZ. The researcher's suggestion for the company is to make improvements to the reward and punishment so that it can be used as a tool to improve the performance of each employee.